PEMBERDAYAAN USAHA KECIL GERABAH MELALUI PROGRAM GLOBAL GOTONG ROYONG (G2R) TETRAPRENENUR MENUJU PRODUK ICONIC GLOBAL DI DESA BANYUMULEK KABUPATEN LOMBOK BARAT - Purwadinata, Subhan; Firmansyah, Muhammad; Hidayat, Ali Akbar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Community Service Partners (PKM), namely the Tourism Aware Youth Group (Pokdarwis) of Pottery Artisans located in Banyumulek Village, West Lombok. Pokdarwis Banyumulek is classified as a pottery craft industry that has not been able to build access to production information, production availability and business processes, so that products are distributed locally even though the product has a high selling value. This lowers the quality and selling value of pottery. The G2RT program is needed to solve the problem of production availability and business processes for craftsmen. The priority problems of partners include problems in the field of education/training as well as problems of business management and business processes. The method used in this PKM activity is carried out through the Global Gotong Royong Tetrapreneur (G2RT) NTB Tetra 1 Entrepreneurial Chain (Chaipreneur) program to become a global iconic product in the form of training and business financial bookkeeping assistance involving key actors of Pokdarwis as facilitators of Banyumulek pottery studies. The target achievement of PKM activities in the 1st year includes: The problem of weak production availability and weak business processes is solved with the implementation of the G2RT Tetra 1 Entrepreneurial Chain (Chaipreneur) program which gives birth to the availability of (1) production facilities to ensure product availability, (2) improvement of business management and business processes in the form of bookkeeping administration and financial statements. The results of PKM activities were created Icon Global standard pottery products from the results of the integration of G2RT Yogyakarta technology transfer with the pottery turntable technology of Banyumulek village potters and the improvement of pottery business management skills by pottery craftsmen. The outputs of this PKM activity are (1) Publication of scientific articles in the journal of BESIRU LPP Manggala Institute (2) Improvement of Partners' knowledge and skills (3) Documentation of service activities in the form of training.